Managing the retro-pathway in direct catalytic asymmetric aldol reactions of thioamides. Issue 11 (7th August 2015) - Bao, Youmei; Kumagai, Naoya; Shibasaki, Masakatsu
Abstract : Thioamides are the preferred pronucleophiles for direct catalytic asymmetric aldol reactions in the context of soft Lewis acid/hard Brønsted base cooperative catalysis. Abstract : Thioamides are the preferred pronucleophiles for direct catalytic asymmetric aldol reactions in the context of soft Lewis acid/hard Brønsted base cooperative catalysis. In-depth investigation of this proton-transfer catalysis, which is virtually in equilibrium, revealed that the prominence of the retro-aldol reaction depended on the substrate combination. The retro-aldol reaction is a serious issue in direct aldol reactions because the product distribution, including enantiomers and diastereomers, is governed by thermodynamic parameters, and the aldol products are obtained in much lower stereoselectivity compared with the kinetically controlled process. Herein we report the beneficial effect of an additive with a functional group architecture similar to that of the aldol adduct that suppresses the retro-aldol reaction by competitively binding to the catalyst. Strategic use of the additive led to high stereoselectivity, even when the combination of substrates was prone to the retro-aldol reaction.